Kajian Ekonomis Pakan Babi Cair Terfermentasi dalam Berbagai Level Biji Asam dan Sumber Protein Berbeda - Wea, Redempta; Ninu, Andy Yumima; Koten, Bernadete Barek (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2022)
A study with the aim of assessing the economic value of fermented liquid pig feed in various levels of tamarind seeds and different protein sources has been carried out from July-August 2022. Liquid feed is formulated according to the needs of the grower phase of pigs. The treatments, Feed A : soybean meal (SM) and Whole tamarind seed (WTS) 0, 10, 20, 30%; Feed B: Meat and bone meal (MBM) and WTS 0, 10, 20, 30%; Feed C: SM and MBM and WTS 0.10,20,30%; Feed D: Fish meal and WTS 0, 10, 20, 30%. The research variables were the price of feed per kg and the total feed costs incurred in rearing grower pigs from weaning until 5 months of rearing reached a slaughter weight of 80 kg. This research is a qualitative research based on the results of the calculation of 4 feed formulations. Data analysis was descriptively by calculating the difference and the percentage of feed costs incurred. The results showed that the decrease in the price of feed per kg and the total cost of feed incurred to reach the slaughter weight of pigs was caused by the use of tamarind seeds which increased up to 30% as well as the price, quality, and type of protein source feed ingredients are used. The conclusion is the use of tamarind seeds in feed with different levels and different protein sources can reduce the price of feed per kg and the cost of feed required to reach slaughter weight.